Late-glacial (Allerod) Coleoptera from Joggins, Lantz and Blomidon, central Nova Scotia, Canada - Miller, Randall (Atlantic Geology, 1997)
Three late-glacial sites in central Nova Scotia, Canada, have produced small Coleoptera assemblages that add to the palaeoenvironmental interpretation during the interval 11,800 to 10,800 years B.P. in the Maritimes region. During this time, beetle assemblages are boreal in nature, in contrast to older sites which contain tundra to tree-line species and later, Younger Dryas age sites, containing northern boreo-montane species. Palaeoentomological interpretations from buried organic sites near Joggins, Lantz and Blomidon are consistent with palynological results from the region and support evidence derived from lake sediments for regional steep climatic gradients during the late-glacial period in the Maritimes.